Risk‐taking behaviours and beliefs about fertility in university students. Issue 23 (19th August 2013) - Gungor, Ilkay; Rathfisch, Gulay; Kizilkaya Beji, Nezihe; Yarar, Makbule; Karamanoglu, Fatma
Abstract : Aims and objectives: To investigate the risk‐taking behaviours and beliefs about fertility among university students in Turkey. Background: Young people are usually ignorant about reproductive health and engage in risky practices. Design: A descriptive cross‐sectional study. Methods: The convenience sample of the study was consisted of 1030 undergraduate students. Data were collected using a self‐administered question form, and students' reproductive health and lifestyle behaviours related with infertility, their beliefs about the risk factors and fertility myths were questioned. Results: The mean age of the students was 20·4 (SD = 2) and ranged between the ages of 16–37. Sexual activity rate was higher among men and 47% of men had more than one sexual partner. Condom use rate was low among women. Underweight was more common among women, while overweight was seen more among men. Students mostly did not exercise regularly. Alcohol was not common, and the rates of smoking were 15% and 23% for women and men, respectively. Only 35–50% of students thought that smoking, alcohol, stress, sexually transmitted diseases, infections, pollution, chemicals, radiation and cancer treatment could be risk factors for fertility. Advanced age and obesity were seen as risk factors for women. Of the students, 50–65% believed that having more than one sexual partner, being underweight, high‐level exercise, excessive caffeine, chronic disease and medications could not have an effect on fertility. Women were more concerned about being infertile, and half of students believed that infertility is preventable. Conclusion: Turkish university students have insufficient knowledge of reproductive health, and they have false beliefs that might affect their risk perception or views about fertility. Relevance to clinical practice: Reproductive healthcare services for young adults should be made more widespread and accessible, and nurses, health providers and instructors should be supportive of them in these matters.